Nama orang Jawa: Kepelbagaian unsur dan maknanya - Sahid Teguh Widodo,; Nuraini Yussof,; Hisham Dzakiria, (Universiti Kebangsaan Malaysia, 2010)
Attempts to comprehend Javanese names can be conducted in many ways. One of the ways is viewing name as a language construction. Name is a compound form composed by the supporting elements. The elements are so inherently constructed that they build up the language structure of the name. The objective of this paper is to understand the variety of the elements of Javanese name. Name is a social product. It is originated from norms, social conventions, group spirits, myths, and cultural selections of the bearer and the maker of the names. Thus, the understanding on the variety of the elements of the Javanese names is very essential to appreciate the social condition from the name perspective